Naturopathic and Herbal Education in Africa: Academic and Legal Perspectives - (:unkn) unknown (My University, 2025)
Background: The evolution of naturopathic and herbal education in Africa is gaining renewed attention amid growing global interest in the integration of complementary and alternative medicine (CAM) with conventional biomedical systems. As African countries seek to formalize and legitimize traditional health knowledge, naturopathic and herbal medicine education emerges as a vital component in reimagining public health systems rooted in cultural relevance and sustainability. Aim of the Study: This study critically examines the academic and legal dimensions shaping the current landscape of naturopathic and herbal medicine education across Africa. It investigates how curriculum structures, institutional development, and regulatory frameworks influence the professionalization and public health impact of these disciplines. Methodology and Methods: The study adopted a qualitative research design using a desk-based/secondary research approach, drawing on documentary analysis of institutional records, policy documents, academic curricula, national qualification frameworks, and relevant legislation across selected African countries. Sampling was purposive, targeting leading institutions, regulatory bodies, and policy frameworks in Ghana, South Africa, Nigeria, The Gambia, and Kenya. Data were analyzed thematically to identify patterns, gaps, and opportunities in educational and regulatory systems, employing a comparative legal and policy analysis lens. Results and Findings: Findings reveal a fragmented yet evolving landscape where significant strides have been made in countries like Ghana and South Africa through the development of national occupational standards, TVET-based frameworks, and institutional accreditation. However, the study identifies regulatory ambiguity in several jurisdictions where naturopathy and herbal medicine remain inadequately distinguished from general traditional medicine. The absence of harmonized legal definitions and inconsistent pra
Keywords: African Research